Comparing the Leverage Effect of Different Frequencies of Stock Returns in an Emerging Market: A Case Study of Pakistan - Rafique, Amir (Information Management and Business Review, 2011)
This study compares the volatility behavior and variance structure of high (daily) and low (weekly, monthly) frequencies of data. The study used seventeen years data from 1991 to 2008 of KSE-100 index. By employing Exponential GARCH (EGARCH) model (asymmetric type GARCH model), the study finds evidence that there are significant asymmetric shocks (leverage effect) to volatility in the three series but the intensity of the shocks are not equal for all the series. The results show that the variance structure of high frequencies data is dissimilar from the low frequencies data.